2003
DOI: 10.1007/bf02982639
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis for the Generation of Hodgkin and Reed-Sternberg Cells in Hodgkin’s Lymphoma

Abstract: Hodgkin's lymphoma (HL) is a lymphoid neoplasm with a low frequency of malignant tumor cells, known as Hodgkin and Reed-Sternberg (H-RS) cells, in a background of mixed cellular infiltrates. Despite extensive studies on H-RS cells, the molecular mechanisms of their growth and regulation have remained uncertain for a long period. Recently, constitutively activated nuclear factor-kappaB (NF-kappaB) was reported to be a unique and common characteristic of H-RS cells that prevents the cells from undergoing apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…31 NF-kB and Ras/Raf/MAPK/ERK are signaling pathways also implicated in the pathogenesis of HL. 2,32 To validate the MS-based protein identification strategy, we used a combination of WB analysis, IFM and IHC analysis for selected candidate proteins (Figure 5a-c). Our studies revealed the expression of BRAF, PIM1 and ErbB-3 in the cell lysate of the HL-derived L428 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 NF-kB and Ras/Raf/MAPK/ERK are signaling pathways also implicated in the pathogenesis of HL. 2,32 To validate the MS-based protein identification strategy, we used a combination of WB analysis, IFM and IHC analysis for selected candidate proteins (Figure 5a-c). Our studies revealed the expression of BRAF, PIM1 and ErbB-3 in the cell lysate of the HL-derived L428 cells.…”
Section: Discussionmentioning
confidence: 99%
“…HL is characterized morphologically by the presence of a distinct population of neoplastic Reed-Sternberg cells (RS), that are surrounded by a non-neoplastic mixed inflammatory infiltrate. 2 Accurate tissue-based diagnosis and staging are critical to the successful treatment of HL. When accurately diagnosed, HL can be treated and cured with local treatment.…”
mentioning
confidence: 99%
“…A similar function has previously been attributed to Reed-Sternberg cells in Hodgkin lymphoma. 49,50 While mutations leading to dysregulation of NF-B activity have been implicated in the genesis of Hodgkin lymphoma, 51 emerging evidence suggests that KSHV-encoded genes may play an analogous role in promoting the stimulation of paracrine secretions in KS. Current efforts are now focused on identifying the KSHV gene(s) responsible for this unique model of paracrine cell transformation.…”
Section: Discussionmentioning
confidence: 99%
“…It activates the majority of signaling pathways that are known to be activated in HRS cells, including NF-κB, PI3K/ Akt/mTOR, and Jak/STAT pathways, thereby induces various antiapoptotic proteins and cytokines (Chen et al, 2003;Lambert and Martinez, 2007;Kung et al, 2011). Since normal germinal center B cells that lack BCR in their cell surfaces are eliminated by apoptosis, the HRS precursor cell is assumed to be rescued by LMP1 that plays a critical role in the protection of B cells from apoptotic death by up-regulating several antiapoptosis genes (Asso-Bonnet et al, 1998;Lee et al, 2003).…”
Section: Ebna1mentioning
confidence: 99%